Demographic and Topographical Trends of Cancer in Nepal: A Five-Year Analysis (2016–2020) - Subedi, Krishna Prasad; Poudel, Rishiram; Thakur, Binay; Bhatta, Pramod; Adhikari, Kishor; Rana, Hari Bahadur (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Cancer is an escalating public health challenge in Nepal. This study analyzes the national cancer burden from 2016 to 2020 using data collected by B.P. Koirala Memorial Cancer Hospital (BPKMCH) under the National Cancer Registry Programme (NCRP). Method: A retrospective descriptive study was conducted on 62,492 new cancer cases diagnosed across Nepal between 1 January 2016 and 31 December 2020. Key variables, including age, sex, address, and cancer site, were recorded and coded according to the International Classification of Diseases for Oncology (ICD-O-10, Third Edition). Data analysis was performed using SPSS version 29.0. Result: Females accounted for 53.6% of cases, with the highest incidence observed in the 60–64-year age group. Urban districts, notably Kathmandu, Jhapa, and Morang, reported the highest case numbers, while remote districts showed lower reporting. Bronchus and lung cancer (12.55%) were the most prevalent overall, followed by breast (9.19%) and cervix uteri cancer (8.33%). Occupational and socio-demographic disparities were observed, with most female patients engaged in housework and males in agriculture. Conclusion: The national cancer burden in Nepal is rising, with pronounced disparities across sex, age, geography, and occupation. Targeted prevention strategies, early detection programs, equitable healthcare access, lifestyle interventions, and HPV vaccination are essential to mitigate cancer incidence and improve public health outcomes.